Pelatihan Akuntansi Dan Keuangan Untuk Peningkatan Kinerja Usaha Mikro Kecil Dan Menengah (UMKM) - Sulastiningsih, Sulastiningsih; Suci Utami Wikaningtyas; Sermi; Darmawan (JCSE: Journal of Community Service and Empowerment, 2024)
The purpose of this Community Service (PkM) program is to provide knowledge, insight and skills regarding accounting practices and financial management to MSME actors in Beringharjo Market who are also partners of BMT Beringharjo Yogyakarta. The activities of this PkM program are by conducting literacy and socialization to MSME actors, conducting training and guidance in preparing financial reports, financial performance analysis, financial planning, management and control. The training method used is by conducting discussions, questions and answers and case analysis. The output of this PkM activity is increasing literacy and application of basic accounting knowledge for MSMEs, increasing understanding, knowledge and application of basic financial management concepts, increasing the competence of small entrepreneurs in preparing financial reports and conducting financial performance analysis.